Pictures and Learning Motivation Towards the Eighth Grade Students’ Writing Achievement on Descriptive Paragraph - Firdaus Firdaus (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
This research was concerned with an inquiry on the effect of the influence of using pictures and learning motivation towards the eight grades Students writing achievements on the descriptive paragraph of SMP Negeri 6 Pagaralam. The problem of this research was to find out whether or not there was an effect of the application pictures towards student's writing achievement on paragraph descriptive. Pictures strategy is a strategy that provides an opportunity for teachers to model exemplary pre-writing behavior and encourages students to set their purposes for writing. This enables students to become more motivated and active in writing a descriptive paragraph. Data collection employed pre-test and posttest for the experimental group. Data analysis was undertaken by using t-test and ANOVA. Findings showed that there was a significant effect of the application of pictures on student's writing achievement on a descriptive paragraph of the eighth grade of SMP Negeri 6 Pagaralam. The conclusion suggests that Ha was accepted while Ho was rejected. It means that using pictures was effective to improve student's writing achievement in a descriptive paragraph.